The determination of Schumann resonance mode frequencies using iterative procedure of complex demodulation - ONDRÁŠKOVÁ, Adriena; ŠEVČÍK, Sebastián (Contributions to Geophysics and Geodesy, 2013)
The more precise determination of instantaneous peak frequency of Schumann resonance (SR) modes, especially based on relatively short signal sequences, seems to be important for detailed analysis of SR modal frequencies variations. Contrary to commonly used method of obtaining modal frequencies by Lorentzian fitting of DFT spectra, the attempt was made to employ the complex demodulation method in iterated form. The results for SR signals contaminated with low-frequency noise and hum in various degree as well as the comparison with standard method are presented. Real signals of vertical electric field component picked up at the Astronomical and Geophysical Observatory of Comenius University at Modra, Slovakia, were the primary sources.